(untitled) (Applied Biological Research, 2015)
Present study was conducted to evaluate anti-reproductive effects of total glycosides of Tripterygium wilfordii (GTW) (Thunder God Vine), in male House rat, Rattus rattus, a predominant rodent pest species found in commensal situations in Punjab, India. Mature male rats were fed on bait (cracked wheat and powdered sugar, 98:2) containing 0.1, 0.2 and 0.3% GTW for 10 days in no-choice feeding tests. Results revealed 67.2- 85.2% acceptability of treated bait over untreated bait. Autopsy of rats after 30 days of treatment withdrawal revealed significant (P≤0.05) reduction in weights of testes and epididymides. The sperm motility, live sperm count and sperm concentration in the cauda epididymal fluid of treated rats was also reduced significantly compared to that in untreated rats. The major abnormality in sperm morphology was sperm head tail separation. Results suggest the use of GTW for reducing reproduction of rattus in integration with chemical control.